Carbon sequestration and environmental impact assessment of jujube cultivation in the Yellow River Jiziwan Basin using life cycle and GIS approaches - Yang Liu; Feihong Liang; Rui Chang; Da Luo; Wei Gao; Denghua Lu; Ning Wang; Mili Liu; Qi Feng; Yizhong Duan (Ecological Indicators)
This study assessed the carbon sequestration potential and environmental impacts of jujube cultivation systems in the Yellow River Jiziwan Basin using an integrated life cycle assessment (LCA) and GIS approach. Field surveys, farmer interviews, and laboratory measurements were conducted to construct a comprehensive life cycle inventory and spatial environmental dataset. Results showed that jujube orchards achieved a net carbon sequestration of 1381.67 × 107 t-C in 2023, equivalent to offsetting the annual CO2 emissions of a 9,265,000 MW thermal power plant. However, significant environmental pressures were identified, particularly aquatic toxicity linked to excessive pesticide use, and nutrient losses resulting in acidification and eutrophication. Sensitivity analysis revealed that northern and eastern regions, benefiting from superior natural conditions, exhibited higher ecological carrying capacities, while southern and western regions were more environmentally vulnerable. Impact response analysis showed that global warming and ecotoxicity indicators were highly sensitive to key input parameters, particularly fertilizer and pesticide use. The study highlights that sustainable management practices—such as optimizing fertilizer and pesticide use, promoting residue recycling, and adapting low-carbon technologies—are critical for enhancing orchard resilience and minimizing carbon footprints. Findings provide practical guidance for sustainable jujube cultivation and broader dryland agricultural transition strategies under climate change scenarios.